Implementation Of The Friday Sermon Program In Strengthening Students' Creed And Moral Values - Miftah Aulia Putri Sinaga; Asnil Aidah Ritonga (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to examine the implementation of the Friday sermon program in strengthening students’ aqidah and moral values at MTs UIN North Sumatra, covering the planning and implementation processes as well as the supporting and inhibiting factors. This research employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving the head of the madrasah, vice principal for student affairs, program supervisors, and students. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation. The findings reveal that the program is planned systematically through stakeholder coordination and implemented continuously as part of religious development activities. The program functions not only as a ritual practice but also as an educational process that promotes habituation, role modeling, and active student participation. Supporting factors include institutional support, supervisor competence, student involvement, and a religious school environment. Inhibiting factors consist of limited facilities, less varied instructional methods, and external influences. The novelty of this study lies in the utilization of the Friday sermon as a student participation-based character-building model. The program contributes to enhancing religious awareness, discipline, responsibility, self-confidence, and strengthening students’ aqidah and moral values.